2019
DOI: 10.1101/735779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemotaxis and topotaxis add vectorially for amoeboid cell migration

Abstract: 3. Data modelling, computational biology and predictive medicine, AbstractCells encounter a wide variety of physical and chemical cues when navigating their native environments. However, their response to multiple simultaneous cues is not yet clear. In particular, the influence of topography, in the presence of a chemotactic gradient, on their migratory behavior is understudied. Here, we investigate the effects of topographical guidance on highly motile amoeboid cell migration (topotaxis) generated by asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Specifically, the topotactic velocity in our simulations is in the order of 1% of the intrinsic particle speed (Fig. 2), whereas in the experiments on cells this ratio is approximately 5%, provided that the obstacles are not spaced further apart than the cell size [15]. In order to better understand this surprising efficiency, the topotactic response of several types of persistently moving cells, such as amoeba [60], cancer cells [61], or leukocytes [62], could be compared.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Specifically, the topotactic velocity in our simulations is in the order of 1% of the intrinsic particle speed (Fig. 2), whereas in the experiments on cells this ratio is approximately 5%, provided that the obstacles are not spaced further apart than the cell size [15]. In order to better understand this surprising efficiency, the topotactic response of several types of persistently moving cells, such as amoeba [60], cancer cells [61], or leukocytes [62], could be compared.…”
Section: Discussionmentioning
confidence: 57%
“…Finally, although here we demonstrated that topotaxis can be solely driven by the interplay between topographical gradients and persistent random motion, whether this is sufficient to explain cellular topotaxis remains an open problem. A quantitative comparison between our numerical data and experiments on highly motile cells [15] shows, in fact, discrepancies that could be ascribed to the enormously more complex interactions between cells and their environment. Specifically, the topotactic velocity in our simulations is in the order of 1% of the intrinsic particle speed (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations